Correlation between microRNA-21 expression and overweight/obesity - Shashwat Sinha; Babu Rajendran; Shomnath Vasagam; Jeyakumar Balakrishnan (Folia Medica)
Introduction: Obesity and overweight are chronic conditions characterized by excessive adiposity that negatively impact health. They are among the most significant risk factors for respiratory failure, diabetes mellitus, cardiovascular disease, and hypertension. Genetic factors may contribute to some of these conditions, but they are mainly associated with the lifestyle in the majority. However, neither genetics nor lifestyle can fully explain all cases. Recent studies have proven that microRNA-21 causes the systemic hypertension, many cardiac pathologies, and some cancers. MicroRNA-21 is viewed as an important future biomarker for many critical conditions. We explored the role of microRNA-21 in the causation of overweight and obesity. There is conflicting data about this association in the literature. Determining if there is an association may help us in better understanding and managing this condition. Aim: To determine if there is a link between microRNA-21 expression and body mass index (BMI) in an Indian adult population. We also compared the lipid profiles (total cholesterol, HDL, LDL, and triglycerides) of participants (grouped by their BMI) to get a better understanding. Patient and methods: The study was conducted in Pondicherry, India and had 50 participants, with 30 as controls having normal BMI, and 20 categorized as overweight or obese as per BMI. Results: The microRNA-21 levels in circulation were analyzed using Real-Time Quantitative Reverse Transcription Polymerase Chain Reaction (qRT-PCR). The expression of microRNA-21 was statistically higher in the overweight/obese cohort compared to the normal BMI individuals (p=0.034). A significant difference was also noted in the total cholesterol levels, with the overweight/obese group having higher values than normal BMI group (p=0.004). Conclusion: This is the first study of its kind in the Indian population to establish that individuals classified as overweight or obese exhibit higher expression of microRNA-21 and elevated total cholesterol levels compared to those with a normal BMI.